The Level of Implementing Governance at Public Jordanian Universities from the Faculty Members' Perspective - Yasar Ali AL-Momani; Mammon Saleem Alzboon; Mustafa Hassan Qwaqzeh (University of Science and Technology, Yemen, 2018)
The purpose of the study was to identify the level of implementing governance in public Jordanian universities from the point of view of the faculty members. The population of the study covered all the faculty members (6926). 243 members were randomly selected from three universities: Jordan, Yarmouk and Mu'tah. The researcher used the descriptive analytical method. The research tool was a questionnaire, which consisted of 50 items, covering 5 dimensions: concept of governance; governance councils; participation; transparency; and accountability. The results of the study showed that the respondents' assessment degree of the level of implementing governance was high. There were also statistically significant differences at the level of (α≥0.05) attributed to the variable of college in favor of humanities. On the other hand, no statistically significant differences were found at the same level of significance attributed to the variables of gender and academic rank. The study recommended that governance should be implemented and spread in public  Jordanian universities. There should also be reforms of the laws and regulations of public Jordanian universities, taking into consideration the conditions of the surrounding environment. Keywords: Governance, Public Jordanian universities, Higher Education.